Adaptive Leadership in Student Organizations: Cultivating Moral Spirit in an Islamic Boarding School - Ika Tiara Aryani; Rohmatun Lukluk Isnaini; Cici Laras Jabil; Luluk Shomitah (Jurnal Isema : Islamic Educational Management, 2026)
This study aims to examine the practice of adaptive leadership in the organization of students of the Nurul Ummahat Islamic Boarding School and its contribution to the formation of student behavior and morals. Adaptive leadership is seen as a relevant approach in responding to the increasingly heterogeneous and critical dynamics of students in the midst of rapid social change. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with student organization leaders (A1), student organization administrators (A2), and non-management students (A3), then analyzed using source triangulation techniques to maintain the credibility of the data. Uniquely, this leadership partice is not merely organizational or managerial, but is deeply rooted in pesantren values and influenced by the moral authority of the Kyai, which shapes leadership as a medium for internalizing islamic moral values among students. This integration distinguishes adaptive leadership in pesantren from general organizational contexts. The results of the study show that adaptive leadership in student organizations is realized through a personal approach, deliberation, moral example, and openness in decision-making. This practice has a positive impact on improving discipline, collective responsibility, and the formation of a collaborative organizational culture rooted in pesantren values.